Optimization of domestic inter-regional virtual water trade of agriculture products in China. Issue 5 (February 2020) - Cai, Rong; Hu, Mengting; Guo, Huiting; Fang, Fei; Liu, Jing; Zhang, Sinan; Bai, Xue; Zhang, Lijia
Abstract: In the face of increasingly severe pressure on water resources, the theory of virtual water and virtual water trade provides feasible solutions for improving the efficiency of global water use for agricultural products and alleviating the pressure on water resources in water scarce countries or regions. Optimizing the domestic inter-regional trade of virtual water trade of agricultural products can provide information to help for the formulation of China's water policy. In this study, we will establish scenarios from the two aspects of economy and water resources allocation and utilization, to study the impact of virtual water trade on water saving of agricultural products trade between regions in China. One scenario does not consider water conservation, only economic revenue - net social revenue maximization scenario. Another way to consider water saving is to maximize water saving. With the maximization of net social revenue, 9.6 billion m3 of virtual water had been exported to other regions in the severe drought regions, saving 18.6 billion m3 of water in China. The net social revenue is 9.1 billion RMB. In the scheme of water-saving maximization, virtual water is exported to water rich regions in severe, moderate and mild drought areas, and China had saved 21.5 billion m3 of water. China's net social revenue is 4 billion RMB. The results show that the optimization of agriculture products domestic inter-regional trade can have a favorable impact on the allocation and utilization of water resources.